The Impact of Labour Market Policies on Productivity in OECD Countries - Andrea Bassanini; Danielle Venn (International Productivity Monitor, 2008)
We investigate the impact of labour market policies on labour and multifactor productivity with industry-level data. First and foremost, labour market policies can influence average measured productivity through their impact on employment. Other things equal, employment growth tends to be associated with lower average measured labour productivity growth as more low-skilled workers enter the workforce. However, policies can also have sizeable direct effects on individual productivity levels and/or growth by creating incentives for workers to invest in training, facilitating reallocation of resources to their most productive uses and generating or maintaining high-quality job matches. We find that employment protection legislation, minimum wages, parental leave and unemployment benefits influence productivity through multiple channels, over and above their impact on employment levels.